DACUM in Terms of Industry-Driven Oriented Training Curriculum on Garment-Related Training Programme in Laos - Meunmany, Santiphap; Khammounty, Bounseng; Maruanaya, Rita Fransina; Haryanto, Didik (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2021)
This study aims to analyse the implementation of the development of a curriculum using the DACUM model in the Vocational Training Program in the garment-related training programme in Laos. The approach in this study is qualitative, using a qualitative descriptive method and the data was obtained through documentation analysis. The results showed that the stakeholders in this development process included government representatives, TVET teachers, in-company trainers, and representatives from TWG of the garment sector. The material for the curriculum meets the requirements of the world of work. Moreover, the tools and equipment of the VTIs themselves might need to be more or be updated already.